Virus Particles from Conidia of Penicillium Species - Sansing, G. A. (1973)
Virus particles and their component double-stranded ribonucleic acid (dsRNA) have been isolated from conidia and mycelia of certain Penicillium species. The conidia and mycelia of P. stoloniferum NRRL 5267 contained 75 and 85 μg of dsRNA/g (dry weight), respectively. Of the total dsRNA released from NRRL 5267 conidia, 10% was nonencapsulated. Conidia of P. brevi-compactum NRRL 5260 and P. chrysogenum Q-176 contained 2 and 120 μg of dsRNA/g (dry weight), respectively, whereas mycelium from the two species contained 3 and 95 μg of dsRNA/g (dry weight), respectively. No viruses were isolated from conidia or mycelia of P. stoloniferum NRRL 859. A method is described for disruption of both conidia and mycelia. The technique facilitates the isolation and characterization of fungal viruses and their component dsRNA and also potentiates surveying of fungal isolates for the presence of virus.